Does a Day Lost Equal Dollars Saved? The Effects of Four-Day School Weeks on School District Expenditures - Paul N. Thompson (Institute of Labor Economics (IZA), 2019)
While cost savings is the primary motivation for the switch to four-day school weeks in many school districts, do these school schedules save school districts any money? To answer this question, this study uses a difference-in-differences analysis using a unique, self-collected longitudinal dataset of four-day school week use from 1999-2015 and National Center for Education Statistics data on school district expenditures. School districts that switch to the four-day school weeks reduce operating expenditures per pupil by 3.1 percent. The largest percentage reductions occur in spending areas where services are reduced one day per week (e.g., food service, transportation), with little to no change in instructional expenditures. Although employment in many of these student service subcategories holds steady after the switch to a four-day school week, some of the burden of reduced service provision is shifted onto hourly workers as spending on employee compensation falls for these types of services.
Keywords: H72; I21; I22; 330; four-day school weeks; school districts; expenditures